Epifluorescencia en la nutrición de larvas de Strombus gigas y Strombus pugilis (Mesogastropoda: Strombidae) - Aldana-Aranda, Dalila (1998)
In order to increase the scientific knowledge about the ingestion and digestion processes of the microalga Tetraselmis suecica by veliger larvae, we did a comparative analisis of feeding kinetics of two Caribbean conch larvae: Queen conch, Strombus gigas, and Pighting conch, Strombus pugilis. These kinetics have been determined in a direct way by means of epifluorescence microscopyc with this technique the potential nutritive value of different microalgae, can be detected in terms of their ingestion and digestion rates. Given the all to fluorescence of algal cells and transparency of both larvae tissues and shell, the algae within the stomach, their lisis and subsequent degradation are observed. The evolution of the ingestion and digestion processes can be follow in live larvae, where other events like the expulsion of intact algae cells initially ingested by the larvae can be observed. The nutritional effects of T. suecica on veliger larvae are explained infunction of a cromatic scale of four nutritional stages, and by means of temporal and absolute ingestion and digestion indices.